HUBUNGAN GINGIVITIS DENGAN PERILAKU MEROKOK PADA SENIMAN PATUNG KAYU DI DESA MAS KECAMATAN UBUD KABUPATEN GIANYAR - I Gede Surya Kencana; I Nyoman Gejir; I Made Budi Artawa (Jurnal Kesehatan Gigi (Dental Health Journal), 2015)
The behavior of smoking is one of cause of some disease especially cancer. Oral chamber is first place of contact of the cigarette smoke with the human body. The cigarrete smoke which flows as the result of the influence of particles of cigarrete smoke. The objective of this study is to identify the correlation of gingivitis with the behavior of wood carvers in Mas Village of Ubud District Gianyar Regency.This study is an observational reseach with cross sectional approach. This size of the sample 30 persons. The analysia being deployed in this research is univariate analysis in the form of frequency aan percentage which subsquently is performed bivariate analysis with Kendalls Tau.Out of 30 respondenDari 30 respondents, it has been found that majority (60%) of the respondents suffer from medium inflammation and none of them have healthy gum.The result of the bivariate analysis show that there is a significant correlation bettwen gingivitis and the quality of cigarettes being consumed in a day with significancy rate 0.000 and correlation rate of 0.516. There is significant correlation bettwen gingivitis with length of smoking time with significancy rate of 0.022 and correlation rate 0.304.There is a significant correlation bettwen gingivitis and behavior of smoking among wood in Mas Village of Ubud District Gianyar Regency.